2005
DOI: 10.1063/1.2008997
|View full text |Cite
|
Sign up to set email alerts
|

Experiments on the effects of aging on compliant coating drag reduction

Abstract: We report the experimental results from a collaborative effort between USA, Russia, and UK on the development of compliant coatings for undersea application of reduction of drag. The focus is on “shelf-life” of coatings. The coatings are based on a linear interference theory of interaction between turbulence pressure fluctuation and the viscoelastic coating. The phase shift between boundary displacement and pressure fluctuation embodies the interference effect. The natural frequency of the coating is matched t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…31 First, selected an approximate linear scatter near the yield point from the tensile strength test. Second, calculated stress (d) and strain (e) according to equations (2) and (3) using these scatter points. Third, plotted strainstress scatter diagrams and performed linear fitting.…”
Section: Tensile Testmentioning
confidence: 99%
See 1 more Smart Citation
“…31 First, selected an approximate linear scatter near the yield point from the tensile strength test. Second, calculated stress (d) and strain (e) according to equations (2) and (3) using these scatter points. Third, plotted strainstress scatter diagrams and performed linear fitting.…”
Section: Tensile Testmentioning
confidence: 99%
“…Most of the researches have focused on the mechanism of skin elasticity [1][2][3][4] and special skin structure 5,6 to control the fluid medium. Some research also indicates that boundary heating mechanism by the dolphin's skin reduces the viscosity of the fluid, which leads to drag reduction, because there is a 9°C difference in temperature between the dolphin's skin and the boundary layer fluid when a dolphin is swimming at high speed.…”
Section: Introductionmentioning
confidence: 99%
“…The slip of a liquid on a solid wall occurs in many engineering situations such as lubrication [1], the flow on porous media [2], coating [3] and particle aggregation [4] and so on. Recently, its use to reduce the frictional drag has drawn attention in the miniaturized devices in which the critical dimension reaches to micro and nano scale [5].…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic properties of these materials such as modulus of elasticity and loss tangent as functions of frequency are of primary importance in designing such devices. In addition, it has been recently reported that information on the dynamic properties is crucial in optimizing design parameters of the compliant coating for the reduction of turbulent flow skin friction [3].…”
Section: Introductionmentioning
confidence: 99%